Turismo agroecológico y su impacto en el desarrollo turístico de la ruta ecológica del cantón Quevedo año 2021 - Anchundia Benavides, Daniela Elizabeth (2022)
Agro ecological tourism is one of the initiatives such as rural tourism where people want to have a connection with the environment as tourists, while influencing the care of nature using ecosystem conservation practices. Tourism planning is developed with several actors, without their integration, it would be impossible to combine new tourism activities and economic growth. But the main problem is that when private initiatives only obtain benefits through the natural environment, this leads to behavior that is not environmentally conscious. The main objective of the research was based on the impact that agro ecological tourism can cause within the Ecological Route of the Quevedo Canton. It has been possible to show in the results of the surveys carried out on the inhabitants of this city that this type of nature-friendly tourism would help not only the economic but also the tourist development of the Canton because both national and foreign tourists would be willing to learn about these new recreation alternatives in the middle of nature.